2010
DOI: 10.1016/j.freeradbiomed.2010.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 in human blood: Native levels and determinants of oxidation during processing and storage

Abstract: Coenzyme Q10 (Q10) is present in the circulation mainly in its reduced form (ubiquinol-10; UL10), but oxidizes quickly ex vivo to ubiquinone-10 (UN10). Therefore, native UL10:UN10 ratios, used as markers of redox status and disease risk, are difficult to measure. We established an RP-(U)HPLC method with coulometric detection to measure natively circulating UL10 and UN10 concentrations by adding a ubiquinol/ubiquinone mixture as an internal standard immediately after plasma preparation. This allowed adjustment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 42 publications
1
40
0
1
Order By: Relevance
“…The redox features of many hydrophilic and lipophilic Q and HQ have been intensively studied by various electrochemical methods [4,19,20,[24][25][26][27][28][29], but surprisingly, there are only few reports related to the electrochemical features of the simplest CoQ member, i.e. CoQ-0 [21][22][23].…”
Section: Voltammetry Of Coenzyme Q-0 In Buffered Water Solutionmentioning
confidence: 99%
“…The redox features of many hydrophilic and lipophilic Q and HQ have been intensively studied by various electrochemical methods [4,19,20,[24][25][26][27][28][29], but surprisingly, there are only few reports related to the electrochemical features of the simplest CoQ member, i.e. CoQ-0 [21][22][23].…”
Section: Voltammetry Of Coenzyme Q-0 In Buffered Water Solutionmentioning
confidence: 99%
“…Previously it has been demonstrated that extracellular supply of coenzyme Q 10 through the circulation influences coenzyme Q 10 levels in blood cells [21] . This may indicate an underlying possibility that coenzyme Q 10 prevents splenomegaly through other mechanism other than its antioxidant capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Mice in the second and third groups were infected with T. b. rhodesiense for 21 and 57 d post infection (dpi) respectively, while those in the first group were uninfected and served as health control for the second and third group. Animals in the third group were projected to survive for 60 dpi after which they were sacrificed at termination of experiment.…”
Section: Infected Untreated Groupsmentioning
confidence: 99%
See 2 more Smart Citations